Komunikasi Organisasi Dalam Sub Bidang Perencanaan PPSDM Geominerba - Zuchril Bintang Luberta; Iin Soraya; Sari Ekowati Hadi (Tamilis Synex: Multidimensional Collaboration, 2024)
Communication consists of various types, one of which is organizational communication, where this communication is carried out both individually and in groups of organizations or agencies. This research is a reference for finding out how communication occurs in an organization using two interrelated theories, namely Laswell’s Theory and SOR Theory which are presented using a qualitative descriptive research method. The organizational communication that will be discussed in this research is PPSDM Geominerba, a government agency that implements organizational communication, because with the many fields within PPSDM Geominerba, PPSDM Geominerba carries out various types of communication. One of the fields in the Geominerba PPSDM is the Planning Sub Sector, where good communication between the leadership and staff is always carried out well, so that it can be an example or reference for every other field within the Geominerba PPSDM agency itself or other organizations or agencies. Because the communication that exists in PPSDM Geominerba is considered good and can be well received by the sender of the message or the person receiving the message, with formal, informal or diagonal communication.